2008
DOI: 10.1016/j.jhealeco.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and immortality: The Nobel Prize as an experiment into the effect of status upon longevity

Abstract: It has been known for centuries that the rich and famous have longer lives than the poor and ordinary. Causality, however, remains trenchantly debated. The ideal experiment would be one in which extra status could somehow be dropped upon a sub-sample of individuals while those in a control group of comparable individuals received none. This paper attempts to formulate a test in that spirit. It collects 19th-century birth data on science Nobel Prize winners. Correcting for potential biases, we estimate that win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 50 publications
5
77
0
2
Order By: Relevance
“…For example, a poor fit between genetic predisposition and occupational choice may result in lower monetary income. In addition, not attaining desired social status can affect life expectancy (Rablen and Oswald 2008) and potentially other non-monetary determinants of utility such as general health. Hence, people may have a genetic predisposition for a particular occupation and there may be a price tag on not finding one's 'occupational destiny'.…”
Section: Conclusion: Genetics In Economics Research?mentioning
confidence: 99%
“…For example, a poor fit between genetic predisposition and occupational choice may result in lower monetary income. In addition, not attaining desired social status can affect life expectancy (Rablen and Oswald 2008) and potentially other non-monetary determinants of utility such as general health. Hence, people may have a genetic predisposition for a particular occupation and there may be a price tag on not finding one's 'occupational destiny'.…”
Section: Conclusion: Genetics In Economics Research?mentioning
confidence: 99%
“…However, identifying the effect of health status on occupational status faces the challenge of circumventing the potential endogeneity (reverse association) between health and occupational status. The literature has partially addressed such endogeneity in different studies that draw on diverse strategies (Rablen and Oswald 2008, Deaton, 2003, Redelmeier and Singh 2001, Smith 1999). …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, cross-sectional correlations between socio-economic status (SES) and health are well established (Marmot, 2003). Evidence from quasi-8 experiments such as Rablen and Oswald (2008) and Redelmeier and Singh (2001) concludes that Nobel Prize and Academy Award are associated with extended longevity. As with the Whitehall study, such evidence has partial external validity given the selected samples (civil servants) the evidence relies on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering Whitehall study demonstrated that health inequalities among civil servants in England correlated with seemingly insignificant differences in social status [10]. A more recent study shows that, among Nobel Prize nominees, those who actually win the prize live on average 2 years longer than those who are nominated but do not win [11]. These and other studies provide evidence that socioeconomic status (SES) influences health outcomes even among relatively affluent individuals who have secure access to medical care.…”
mentioning
confidence: 88%